Circulating Methemoblogin Fraction in Dogs With Sepsis - Troia, Roberta; Ciuffoli, Elena; Vasylyeva, Kateryna; Foglia, Armando; Dondi, Francesco; Giunti, Massimo (Frontiers in Veterinary Science, 2020)
Large amount of nitric oxide (NO) can be released in patients with sepsis. Methemoglobin is formed from the interaction between NO and hemoglobin. Mild methemoglobinemia reflecting NO overproduction has been reported in septic people, and occasionally associated to septic shock and organ dysfunction. The aim of this retrospective study was to evaluate circulating methemoglobin fraction in dogs with sepsis and to assess its prognostic value. Methemoglobin reference interval (RI) was calculated in 41 healthy dogs and was set at 0-2.2%. A total of 131 dogs with sepsis were included in the study; 24/131 had a circulating methemoglobin ≥2.2%. The median methemoglobin fraction was significantly higher in dogs with sepsis compared to healthy ones (1.7%, 0.4-3.5% vs. 1.0%, 0.3-2.2%, P = 0.0005). No significant difference was observed between dogs with uncomplicated sepsis (n=98) vs. dogs with septic shock (n=33) (1.8%, 0.4-2.8% vs. 1.5%, 0.4-3.5%, P=0.74), between dogs with and without multi-organ dysfunction (n=38 and n=93, respectively) (1.7%, 0.4-3.5% vs. 1.7%, 0.5-2.8%, P = 0.27), and between survivors (n=77) vs. non survivors (n=54) (1.5%, 0.4-2.8% vs. 1.8%, 0.4-3.5%, P = 0.05). Dogs with methemoglobin fraction above or equal to the upper limit of the RI had a significantly higher frequency of death compared to dogs with methemoglobin levels <2.2% (60.0% vs. 36.8%, P = 0.04). In conclusion, mild methemoglobinemia is detected in dogs with sepsis, and methemoglobin values above the RI might be associated with a worse outcome.